Assessment of a typical antipsychotics induced Metabolic syndrome among South Indian patients with psychiatric illnesses - NIVEDITHA P; NANISHA N V; MONISHA S; SUMA SRI N; PADMAPRIYA C; VANITHA RANI N; THENNARASU P (International Journal of Pharma and Bio Sciences, 2019)
Atypical antipsychotics are commonly prescribed for psychosis and metabolic Syndrome has a strong relationship with atypical antipsychotic usage. A prospective study was done to assess the incidence of metabolic syndrome and its components in Psychiatric patients on atypical antipsychotics. Blood pressure, body weight, Body Mass Index and waist circumference were calculated and a 5 ml of venous blood was collected at baseline, and for 12 weeks it was follow up to determine the fasting lipid profile and blood glucose levels. Difference in values, from baseline to follow up was assessed using statistical tools. Metabolic syndrome was assessed using International Diabetes Federation criteria. Of 96 patients, 53 were male and 43 were female. Majority (40%) were in the age range of 26 to 35 years. Patients were given Olanzapine, Quetiapine, Risperidone per oral as monotherapy and Risperidone with Olanzapine or Quetiapine as combination therapy per orally. Changes observed from baseline to follow up included weight gain (89%), increase in BMI (78%), waist circumference (91%), FBS (60%), triglycerides (95%) and decreased HDL (65%) but no changes were observed in blood pressure. Olanzapine was found to cause weight gain both as single (32%) and in combined therapy (15%). Increased waist circumference was observed with all the three drugs. The study identified 5% of patients with metabolic syndrome as per criteria. Duration of antipsychotic usage had a positive correlation with alterations in the metabolic components. Gender had no statistically significant influence over the risk for metabolic syndrome. Early identification of metabolic syndrome and therapeutic intervention in Psychiatric patients on atypical antipsychotics may reduce long term morbidity.